2021
DOI: 10.21037/qims-20-1156
|View full text |Cite
|
Sign up to set email alerts
|

Multi-detector computed tomography (MDCT) imaging: association of bone texture parameters with finite element analysis (FEA)-based failure load of single vertebrae and functional spinal units

Abstract: Background: Osteoporosis is a systemic skeletal disease that is characterized by low bone mass and microarchitectural deterioration, predisposing affected individuals to fragility fractures. Yet, standard measurement of areal bone mineral density (BMD) in dual-energy X-ray absorptiometry (DXA) as the current reference standard has limitations for correctly detecting osteoporosis and fracture risk, with opportunistic osteoporosis screening using computed tomography (CT) showing increasing importance. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…(1)Patient with fresh vertebral fractures with bone marrow edema confirmed by thoracic/lumbar MRI. Bone marrow edema was identified as significantly high signal on STIR and T2WI sequences and low signal on T1WI; (2)with chest/abdominal CT scans within 48 h of the MR examination; (3) Patients with at least one fresh fracture vertebra recognized as OVFs ,that is the fractural vertebral without visual reduction in height (Genant grade = 0) on initial CT imaging [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)Patient with fresh vertebral fractures with bone marrow edema confirmed by thoracic/lumbar MRI. Bone marrow edema was identified as significantly high signal on STIR and T2WI sequences and low signal on T1WI; (2)with chest/abdominal CT scans within 48 h of the MR examination; (3) Patients with at least one fresh fracture vertebra recognized as OVFs ,that is the fractural vertebral without visual reduction in height (Genant grade = 0) on initial CT imaging [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Zaworski et al [ 11 ] found that MRI-based TA of trabecular bone could evaluate vertebral bone fragility while discriminating between osteoporosis patients with or without a history of fracture. Sollmann et al [ 12 ] reported that some texture features, based on CT of the vertebral body, showed a strong correlation with finite element analysis results, indicating that radiomics parameters can be used to evaluate the vertebral load. Tabari et al [ 13 ] demonstrated that some texture parameters of vertebral trabeculae on lumbar spine CT in patients with anorexia nervosa were different than those in the healthy control group, suggesting that TA might provide information about bone health.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the distribution of gray-level values, texture analysis was used to characterize structural image properties of predefined regions by quantifying different texture features (37)(38)(39). Texture analysis was performed using the segmentation masks derived from CT and CSE-MRI enclosing single vertebral bodies, and different first-order statistical moments from global gray-level histograms, second-order features based on the graylevel co-occurrence matrix (GLCM), and higher-order features based on the gray-level run-length matrix (GLRLM) were extracted (Figure 1 and Table 1) (40,41,51,(53)(54)(55).…”
Section: Texture Analysismentioning
confidence: 99%